MOORA sebagai Sistem Pendukung Keputusan dalam Mengukur Tingkat Kinerja Dosen - Arista, Ruly Dwi (SAFE-Network, 2020)
Education personnel (Lecturers) are the most important assets owned by a university. To measure the performance level of lecturers, the campus management conducts performance appraisals for each of its lecturers' work at the Panca Budi University Development, Medan. The purpose of this research is to assist decision making in measuring the level of lecturers who perform well at Panca Budi University Development. The data used in this study are data taken from the Panca Budi Development University. Lecturer data that is processed is as many as 20 permanent lecturers who have been registered at the Panca Budi Development University (UNPAB) Medan. processing by using the Multi Objective Optimization method On The Basic Of Ratio (Moora). The results of the testing of the Morra method obtained the highest value of the alternative table calculation, namely M3 (0.2144), the lecturers with good performance are M3 Based on the results of the research conducted, the application of the Multi Objective Optimization method on the Basic Of Ratio (Moora) is quite easy. used as a way in the process of measuring the level of lecturer performance.